'Teachers are Always Good. Children have Flaws.': Memories of School and Learning in the Narratives of Low-income Parents in India. (March 2014) - Ganapathy-Coleman, Hemalatha
What do the poor in India say about the education their children are receiving? And how do they remember their own years of schooling? This cultural psychological study of parental beliefs about education explored these questions by employing participant observation, in-depth interviews, focus groups and sentence-completion tasks. The participants were 19 low-income parents from the state of Gujarat, India, with a child between 8 and 18 years of age. Results indicated that these materially impoverished parents nostalgically deified teachers, whom they often referred to as Guru, while they characterised their young student selves as playful and distracted. They upheld the sanctity of the teacher–student relationship, only occasionally criticising the schools and teachers of their childhood. Examining the personal narratives of these parents, I argue that Guru is a shared cultural concept that they have appropriated as a cultural resource for understanding their own educational experiences and reconstructing their childhood selves in acts of remembering. Upholding this ancient concept also allows them to stake a claim to their ethnocultural belonging in the present.